2020
DOI: 10.3390/sports8020021
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Novice Participants during an Eight-Week Start up CrossFit Program—A Prospective Cohort Study

Abstract: Background: Previously published studies have reported injury rates ranging from 0.74 to 3.3 per 1000 h of exposure in CrossFit participants. However, the existing body of evidence is mainly based on experienced participants; therefore, the injury incidence and injury rate within novice CrossFit participants remains relatively unknown. The aim of this study wasto investigate the injury incidence and injury rate among novice participants in an eight-week CrossFit program. Methods: This survey-based prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 20 publications
0
50
0
4
Order By: Relevance
“…To prevent injuries, the scope and intensity of the exercises in the CrossFit must be increased slowly, scalable and carefully. At this point the injury reducing influence of supervision by qualified coaches becomes apparent [40] ; especially among novice participants who seem more prone to injury than experienced participants [21] . Also, this includes the adequate exercise selection for females with urinary incontinence problems which are more likely to occur in CrossFit [6] .…”
Section: Future Directions and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent injuries, the scope and intensity of the exercises in the CrossFit must be increased slowly, scalable and carefully. At this point the injury reducing influence of supervision by qualified coaches becomes apparent [40] ; especially among novice participants who seem more prone to injury than experienced participants [21] . Also, this includes the adequate exercise selection for females with urinary incontinence problems which are more likely to occur in CrossFit [6] .…”
Section: Future Directions and Implicationsmentioning
confidence: 99%
“…Previously published studies have reported injury rates ranging from 0.74 to 3.3 per 1000 h CrossFit training ( [9] , [15] , [21] ). On the basis of these studies, the injury incidence in CrossFit is comparable or slightly higher to related sports, including gymnastics, weightlifting and powerlifting with a 2b evidence level [5] , [15] , [20] ), but lower than in game sports and other traditional sport disciplines [35] .…”
Section: Crossfit - Incidence and Location Of Crossfit Related Injurimentioning
confidence: 99%
“…(5)(6)(7) However, no evidence that CrossFit is associated with a higher incidence of injuries relative to other sports has been given so far and the rate of CrossFit-related injuries (0.74 to 3.3 per 1,000 hours of training) is similar to sports such as weightlifting, gymnastics and tennis. (5,8,9) Risk factors for higher incidence of CrossFit-related injuries are athletic skills, hours of training, participation in competitions and trainer supervision. (5)(6)(7) CrossFit has appealed to physically active as well as sedentary individuals.…”
Section: ❚ Resumomentioning
confidence: 99%
“…Aus diesem Grund wurden verschiedene Studien aus unterschiedlichen Ländern zur Häufigkeit und Ursache von Verletzungen im CF durchgeführt, u. a. in Dänemark, Brasilien, Italien, den Niederlanden, Portugal und den USA [12], [13], [14], [15], [16], [17] (p = 0,778). Teilnehmer mit mehr als 6 Monaten Trainingserfahrung verletzten sich signifikant häufiger (≤6 Monate: 0,4 ± 0,6 Verletzungen; >6 Monate: 0,7 ± 0,8 Verletzungen; p = 0,002).…”
Section: Was Istunclassified
“…Teilnehmer mit mehr als 6 Monaten Trainingserfahrung verletzten sich signifikant häufiger (≤6 Monate: 0,4 ± 0,6 Verletzungen; >6 Monate: 0,7 ± 0,8 Verletzungen; p = 0,002). [12], [16] (▶Abb. 4).…”
Section: Was Istunclassified